MIXED CORE SUBCHANNEL MODEL FOR SUBCAL AND COUPLING WITH ANDREA - Vojtěch Caha; Jiří Čížek (Acta Polytechnica CTU Proceedings)
This paper presents the results of an analysis of flow distribution in VVER-1000 mixed core consisting of fuel assemblies with non-identical spacing grids. The calculation was carried out using the modified subchannel code SUBCAL-AZ which allows to calculate 3D thermal-hydraulic characteristics of the coolant flow in the full core subchannel model coupled with the neutron-physical code ANDREA. This full core subchannel model was created in three variants depending on the ANDREA calculations. The first variant (homogeneous core) consisted of 163 hydraulically identical fuel assemblies TVSA-T mod.2, whereas the other variants (mixed cores) consisted of fuel assemblies TVSA-T mod.0, mod.1 and mod.2. These fuel assemblies mainly differ in types, number and axial coordinate of spacing grids and also in diameter of guide tubes. The influence of mixed core to flow distribution was obtained by comparing these variants.